WEB-BASED EQUIPMENT INVENTORY INFORMATION SYSTEM IN THE SERVICE DIVISION OF PT ARISTA SUKSES MANDIRI JAKARTA - Anggi Oktaviani; Muhammad Nogie; Deny Novianti (Jurnal Riset Informatika, 2020)
Work equipment inventory management at the service division of PT. Arista Sukses Mandiri Jakarta is still done manually using printed forms (for daily checks) and handwritten books (which record every piece of equipment that enters and/or leaves the warehouse), therefore personnel needs more time to carry out these activities. Equipment inventory management must be correct and precise between existing data and the reality in the field, but if it is carried out manually the risk of data error is higher than if it is carried out using a computerized system. Also, using a computerized system in an equipment inventory environment can make the process faster, thus achieving time efficiency. The web-based inventory system was developed by the author (as well as the developer) to solve or at least reduce the problem. The model used in the development of this web-based application system is a waterfall development model with whirlpools for beginners as suggested by Powel et al. This model consists of problem definition, needs analysis, prototype design, implementation, integration/testing, release/maintenance. The final product of research and development written in this paper is a web-based application for work equipment inventory that can make the process faster, precise, and efficient.